Penegakan Hukum Dalam Rangka Pemberantasan Praktek Illegal Logging Di Kalimantan Timur - Siti Kotijah (Jurnal Risalah Hukum, 2006)
Forest as a renewable natural resource has given a great implication on human’s life. Illegal logging has caused many destructions and imbalanced ecosystem which give bad impact to our surroundings. The law enforcement concerning this matter should be in line with the existing regulations so there will be an assurance for a legal action taken to those comitting this illegal logging crime. Several existing obstacles such as licensing problems, forest control, officers involvement as well as law consistency are a challenge that must be solved to fight against illegal logging in East Kalimantan. Key Word : Forestry , Illegal Logging, Law Enforcement